Jamaica : Poverty and Social Impacts of Fiscal Reforms - World Bank (Washington, DC, 2013)
This Poverty and Social Impact Analysis (PSIA) explores the distributional effects of a package of fiscal reforms initiated by the Government of Jamaica and supported by the World Bank under the programmatic fiscal sustainability Development Policy Loan (DPL) series. The DPL series supports improved budget and debt management in order to reduce the debt overhang and create additional fiscal space for productive public spending, including social expenditures. The PSIA discusses the poverty and distributional impacts of the prior actions supported under the DPL, with a particular focus on two reform actions likely to have the most significant impacts: (1) tax reform and (2) public sector reform, focusing on rationalization of public bodies. The report offers both quantitative and qualitative assessments of the potential poverty and distributional effects of these policy changes. The report is structured as follows: section two analyzes the expected impact of changes in tax policy; section three investigates the potential impacts of public bodies' rationalization, and section four offers some caveats and concluding remarks. Each section begins with a discussion of the reform background as well as the major supporters and opponents of the reform. The analysis in each section is presented with the least possible amount of technical details in order to maximize the appeal to a broader audience. For the interested reader, the methodological details of the empirical approaches employed in this report are contained in the annexes.